Anti‐melanoma differentiation‐associated protein 5 autoantibodies as a marker for dermatomyositis‐associated interstitial lung disease. (27th February 2017) - Jordan, M.; Ghoreschi, K.
Abstract : Linked Article: Matsushita et al. Br J Dermatol 2017; 176:395–402 .